Hyponatraemia and dehydration in severe malaria. Issue 3 (March 1996) - English, M C; Waruiru, C; Lightowler, C; Murphy, S A; Kirigha, G; Marsh, K
Abstract : The prevalence and likely cause of hyponatraemia in severe childhood malaria were investigated. One hundred and thirty two children, 47 of whom had cerebral malaria, were prospectively recruited and serial simple indices of fluid and electrolyte balance and renal function monitored during admission. In 55%, hyponatraemia (sodium < 135 mmol/l) was present on admission. Hyponatraemia was pronounced (sodium < or = 130 mmol/l) in 21%, and these children gained less weight during admission (mean weight gain 2.4% v 4.3%) than children with a normal sodium (135-145 mmol/l). Overall, 31% of survivors were at least moderately dehydrated on admission (5% weight gain by discharge). These children had higher plasma urea concentrations on admission (6.1 v 4.5 mmol/l) and were more acidotic (mean base excess -12.1 v -8.0) than children who were not dehydrated. There were changes in simple indices of renal function between admission and discharge in children who survived (creatinine 65.7 v 37.9 mumol/l and urea 5.5 v 1.9 mmol/l). The results suggest that dehydration is common in severe childhood malaria, that it may contribute to mild impairment in renal function, and that hyponatraemic children are less water depleted, showing appropriate rather than inappropriate secretion of antidiuretic hormone.